The Role of Accounting Information Systems as Business Strategy at Madiun City - Halleina Rejeki Putri Hartono; Ridho Muarief; La Ode Abdullah; Nova Maulud Widodo; Yana Dwi Christanti; Yudha Nauval Prastyanika Putra (International Journal of Economics, Management and Accounting, 2024)
This study aims to determine the implications of accounting information systems (AIS) as a business strategy for SMEs in Madiun City. Economic digitalization has a major effect on SMEs. One of the implications (Angelina Wijaya Tan et al., 2024) of this economic digitalization is the transformation carried out by SME actors into the digital era, including the use of Accounting Information Systems (AIS). Efficiency is needed by SMEs in order to keep up with the changing times. The use of this AIS can improve the reporting process and business processes carried out by SMEs. Another advantage (Ari Rohmana & Hwihanus Hwihanus, 2023) of using this AIS is to avoid recording errors and reduce waste. It can be seen that AIS has an important role in the business processes carried out by SMEs. The research method used is qualitative research. The respondents used were SMEs in Madiun City.